2020
DOI: 10.1007/978-3-030-48439-2_47
|View full text |Cite
|
Sign up to set email alerts
|

Can Autonomous Ships Help Short-Sea Shipping Become More Cost-Efficient?

Abstract: There is a strong political focus on moving cargo transportation from trucks to ships to reduce environmental emissions and road congestion. We study how the introduction of a future generation of autonomous ships can be utilized in maritime transportation systems to become more cost-efficient, and as such contribute in the shift from land to sea. Specifically, we consider a case study for a Norwegian shipping company and solve a combined liner shipping network design and fleet size and mix problem to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Other research performed into the economic feasibility of unmanned ships leans heavily on this research as it is detailed and covers many aspects (Kooij et al, 2021;Ziajka-Poznańska & Montewka, 2021). Other research into the economics of unmanned ships mainly focusses on the possibility of adding these vessel types into an existing infrastructure (Akbar et al, 2021;Msakni et al, 2020).…”
Section: Economic Feasibilitymentioning
confidence: 99%
“…Other research performed into the economic feasibility of unmanned ships leans heavily on this research as it is detailed and covers many aspects (Kooij et al, 2021;Ziajka-Poznańska & Montewka, 2021). Other research into the economics of unmanned ships mainly focusses on the possibility of adding these vessel types into an existing infrastructure (Akbar et al, 2021;Msakni et al, 2020).…”
Section: Economic Feasibilitymentioning
confidence: 99%
“…One document presents literature analysis on selected aspects of autonomous shipping in terms of design, safety, navigation control, and short description of economic issues [39]. The rest of the papers focus on the Liner Shipping Network Design concept [23,40] and vessel platooning concept [41].…”
Section: Case Studymentioning
confidence: 99%
“…Then it would be extr challenging for the vessel to be cost-competitive, unless she would be operated exclu in SECA zones (Sulphur Emission Control Area). When it comes to various modes of autonomous ship operation, the liner shi network design concept demonstrated that its introduction is economically favou [23,40]. The authors also presented the sensitivity analysis for the case of a conven mother vessel and autonomous daughter vessels.…”
Section: Sensitivity Analysis Of a Life-time Cost Assessmentmentioning
confidence: 99%
See 1 more Smart Citation